Digital storytelling to enhance English language students’ understanding of climate change mitigation: A linguistic evidence - Purnama Rika Perdana; Ristha Sukmalasari; Siti Suharsih; Siti Aishah Md Yusop (English Department - University of Sultan Ageng Tirtayasa, 2025)
Digital Storytelling (DS) is an innovative learning approach that integrates technology and digital narratives to enhance students’ engagement, critical thinking, and environmental awareness. The study explores the role of Digital Storytelling (DS) in fostering students’ ability to connect real-world issues with academic learning, particularly in language education. This study employs an exploratory approach using qualitative research. Data is collected through classroom observation, semi-structured interviews, and analysis of students' narratives. The findings reveal that DS effectively enhances students' engagement and cognitive processing by incorporating collaborative storytelling, multimedia elements, and interactive learning experiences. DS encourages students to participate in discussions actively, express their perspectives through digital media, and build deeper connections with complex global issues beyond traditional learning approaches. This study concludes that DS is a powerful educational tool that supports independent learning, fosters meaningful engagement, and aligns with the Merdeka Curriculum’s vision of equipping students with competencies relevant to 21st-century education.